(untitled) (Window of Public Health Journal, 2026)
The elderly are a vulnerable group that requires high-quality, friendly healthcare services. This study aims to determine the relationships among waiting time, waiting room comfort, and elderly patient satisfaction at the Outpatient Installation of Labuang Baji Regional Hospital, Makassar City. This study used a quantitative cross-sectional design. A sample of 190 elderly patients was selected using cluster purposive sampling from three clinics with the highest number of visits. Analysis was performed using the chi-square test. The independent variables were waiting time and waiting room comfort based on three servicescape dimensions (surrounding environment, layout and functionality, symbols and signs). The dependent variable was elderly patient satisfaction. The results of the bivariate analysis showed a significant relationship between waiting time and the three dimensions of waiting room comfort, as well as elderly patient satisfaction (p < 0.05). This study concluded that reducing waiting time and increasing waiting room comfort improve elderly patient satisfaction. The main problem identified in this study was the low level of elderly satisfaction, influenced by the length of wait and the discomfort of the waiting room. This condition indicates that the elderly need a service environment that is more responsive, safe, and friendly to their physical limitations. This study also provides several recommendations, including improving queue management, optimizing waiting room facilities, and improving communication and support for elderly patients during the service process.